2018
DOI: 10.1111/jdi.12891
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the 2016 Kumamoto Earthquake on glycemic control in patients with diabetes

Abstract: Glycemic control, associated factors and stress levels are altered in chronological order. Post-disaster diabetic medical care must consider these corresponding points in accordance with the time-period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 13 publications
(20 reference statements)
0
22
0
Order By: Relevance
“…In addition, stress is thought impact that metabolic parameters in patients with diabetes mellitus [20]. In previous studies, it has been reported that disasters, including earthquakes, floods, and hurricanes, were associated with increased stress and worse glycemic control in patients with type 2 diabetes mellitus [10,[21][22][23][24][25][26][27]. Although the association between stress and glycemic control was not observed in this study, unlike these previous disasters, the COVID-19 pandemic is ongoing and there are concerns that the impact on patients with diabetes mellitus will continue or become more severe.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, stress is thought impact that metabolic parameters in patients with diabetes mellitus [20]. In previous studies, it has been reported that disasters, including earthquakes, floods, and hurricanes, were associated with increased stress and worse glycemic control in patients with type 2 diabetes mellitus [10,[21][22][23][24][25][26][27]. Although the association between stress and glycemic control was not observed in this study, unlike these previous disasters, the COVID-19 pandemic is ongoing and there are concerns that the impact on patients with diabetes mellitus will continue or become more severe.…”
Section: Discussionmentioning
confidence: 99%
“…For example, patients with diabetes lose their insulin due to disasters (Fujihara et al, 2012; Kishimoto & Noda, 2013; Tanaka et al, 2015), which results in a more serious condition due to the discontinuation of insulin injections (Kishimoto & Noda, 2013). Patients with diabetes also struggled with unhealthy diets during disaster (Allweiss & Albright, 2011; Kondo et al, 2019). Considering these past experiences of disasters, it makes sense for the participants to be aware of insulin and food.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with type 2 diabetes, however, blood glucose control seemed initially improved, followed by aggravation as a result of a shortage of medications and foods. These are very valuable findings to take into account in actual planning for disasters 12 .…”
mentioning
confidence: 90%